1990
DOI: 10.1128/jcm.28.2.182-187.1990
|View full text |Cite
|
Sign up to set email alerts
|

Serological typing of Branhamella catarrhalis strains on the basis of lipopolysaccharide antigens

Abstract: Branhamella catarrhalis from different parts of the world were serologically typed according to their lipopolysaccharide (LPS) antigenicity. For this purpose, an inhibition enzyme-linked immunosorbent assay was developed using the following reagents: antisera raised against whole bacterial suspensions for a panel of 16 serotype strains and LPS prepared from these strains by phenol extraction. Antisera were absorbed with whole bacterial suspensions of the B. catarrhalis strains to be tested. The residual activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…The outer-membrane glycolipids of M. catarrhalis lack the repeating O-antigen polysaccharides of LPS and are hence designated lipo-oligosaccharides (LOS) [38]. These occur commonly in nonenteric Gram-negative bacteria, such as those that colonize the mucosal surfaces of the upper respiratory tract [39].…”
Section: Discussionmentioning
confidence: 99%
“…The outer-membrane glycolipids of M. catarrhalis lack the repeating O-antigen polysaccharides of LPS and are hence designated lipo-oligosaccharides (LOS) [38]. These occur commonly in nonenteric Gram-negative bacteria, such as those that colonize the mucosal surfaces of the upper respiratory tract [39].…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the infectious process of M. catarrhalis and the mechanisms involved in the host protection are therefore limited. The targets for a protective immune response have not been identified, but the homogeneous composition of the outer membrane proteins and the lipopolysaccharide of M. cutarrhalis suggest that an antibody response to one strain may protect against others (1,24). However, the immune response to the organism seems to be poor, and young children fail to develop a systemic antibody response in a uniform manner after a middle ear infection (5,15).…”
mentioning
confidence: 99%
“…21-30) may depend on cross-reactions with LPS of other bacteria, which makes the use of LPS-ELISA less specific. It has previously been shown that the LPS of M. catarrhalis displays different antigenic specificities (22). However, as we have shown in an earlier study, the human antibody response to the LPS antigens of M. cutarrhalis appears to be of low specificity (2 1).…”
Section: Discussionmentioning
confidence: 60%
“…A cross-reaction with Streptococcus pyugenes, which was demonstrated with rabbit antisera against nine strains of M. catarrhalis, was less pronounced with this strain than with most other strains (16). The LPS antigen was prepared from a reference strain belonging to type A (22), since this is the most common serotype. Based on previous studies (21) the inclusion of other serotype LPS preparations was not considered necessary, since the human antibody response to the M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation